Development of Picture Book Media for Expressive Language Skills of Children With Autism - Resha Fitria Suistika; Ishartiwi Ishartiwi (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
The expressive language skills of children with autism can be improved through teaching and learning. One of the factors supporting the success of teaching and learning process in improving the expressive language skills of children with autism is the selection of media which is in accordance with the characteristic of children with autism as target of learning. Children with autism are known to conceive information based on visual as their characteristic, so visual-based media will be more effectively in the learning process. This study uses the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model that aims to develop visual-based media that can accommodate the expressive language skills of children with autism. The media developed is in form book-shaped media that contains a combination of writing and image illustration. This study produces a decent picture book media based on material conformity with curriculum, grammar used, media display, and communication theory used.